Store Image and Store Choice Decision: An Investigation of Consumers’ Choice Shopping Behavior in Malaysia - Muhamad Jantan; Abdul Razak Kamaruddin (Asian Academy of Management Journal, 1999)
The retail sector in Malaysia has been experiencing tremendous changes since the 1950's except for the survival of wet market (a traditional market comprising of small family-run stalls), conventional Mom-and-Pop shops, and the night bazaars (mobile independent retailers) which uniquely co-exist in the retailing environment (Zain & Rejab, 1989). Supermarkets and departmental stores has gradually become a common form of retail outlet even though they have encountered a series of closures mainly due to the competetive environment. In the early 1980's, there was a sudden influx of retail outlets and in a recent account there was about seven million sq.ft. of retail space in Malaysia. It is expected that this will increase to 27 million sq.ft. in the next three years ( New Straits Times. 1995)